Guizhi decoction combined with Guizhigancaolonggumuli decoction in the treatment of insomnia: A case report (桂枝汤合桂枝甘草龙骨牡蛎汤加减临床治疗失眠症1例) - ZOU Ling (邹玲); XIAO Zhouhua (肖周华) (中西医结合护理)
This paper summered the clinical application of Guizhi decoction combined with Guizhigancaolonggumuli decoction in treating one case of insomnia. Based on the Traditional Chinese Medicine syndrome differentiation, Guizhi decoction combined with Guizhigancaolonggumuli decoction was administrated orally, and comprehensive nursing interventions on environment, dietary, exercise, mental health of the patient were carried out to improve the sleep quality of the patient. (本文总结1例采用桂枝汤合桂枝甘草龙骨牡蛎汤加减治疗失眠患者的临床经验。失眠患者多为阴阳不调, 久则易伤阴阳, 故而引起“不寐”。基于中医辨证分型, 桂枝汤合桂枝甘草龙骨牡蛎汤加减, 温补心阳, 调理营卫, 使阴阳调和, 并配合环境、饮食、运动、心理等护理干预, 有效改善了患者睡眠质量。)